Experimental Method and Characterization of Friction Properties between Woven Fabric and Human Skin in Wet Condition (Journal of Fiber Bioengineering and Informatics, 2018)
In order to measure the friction force between woven fabric and skin at a wet condition, it was proposedthat the completed wetting woven fabric could be hung on the line for different times to reach the differentwet conditions. According to the water loss characteristic of woven fabric, the relative hanging time wasused to describe the different wetting rates. The friction curves between 20 kinds of woven fabric andhuman skin were measured by the independently developed fabric-skin friction tester at 6 kinds of wetconditions. It was found that there were 4 kinds of friction-sliding displacement curves. They werenormal friction curve, arched friction curve, rising friction curve and decline friction curve. Accordingto the characteristic of various friction curves, 7 kinds of friction indices were defined to characterize thefriction properties between woven fabric and skin at wet conditions. They were static friction, turningpoint between static friction and dynamic friction, average dynamic friction and its coefficient of meandeviation, maximum dynamic friction force, variation rate of dynamic friction and friction coefficient.Besides, it was also found that normal friction curve and rising friction curve usually occurred and theirappearing probabilities were 44% and 47%, respectively.
Keywords: Woven Fabric; Human Skin; Friction; Testing Method; Wet Condition; Hanging Time